Pengaruh Pengalaman Kerja, Promosi Jabatan dan Pengembangan Karir Terhadap Kepuasan Kerja Karyawan pada PT. X - Yulainda Yulainda; Akhirman Akhirman; Firmansyah Kusasi (Bahtera Inovasi, 2018)
The purpose of this research is to know whether the Work Experience, Job Promotion and Career Development influence Employee Job Satisfaction at PT. X. The type of data that is used consists of primary data and secondary data, obtained by interview, questionnaire distribution and study of library, which the measurement uses Likert scale, and processed with SPSS version 22 program. The sample technique uses non- probability sampling totaling 40 respondents distributed to all employees of PT. X. Data analysis method used is quantitative analysis using data quality test, classical assumption test and hypothesis testing analysis. The research results indicate that: (1) Work Experience there is a significant influence between Work Experience variables on employee job satisfaction at PT. X, (2) Position Promotion there is a significant influence between Job Promotion variables on employee job satisfaction at PT. X, and (3) Career Development there is a significant influence between Career Development variables on employee job satisfaction at PT. X.